PEMBUATAN MODEL CRM PADA PENGEMBANGAN E-GOVERNMENT DINAS KELAUTAN DAN PERIKANAN DIY MENGGUNAKAN COBIT 4.1 PADA DOMAIN DELIVERY AND SUPPORT (DS) - Imam Ghozali; Sri Handayaningsih; Tedy Setiadi (Jurusan Teknik Informatika, 2016)
The development of information systems at the Department of Marine and Fisheries (Dislautkan) DIY basically developed but not optimally yet. Information systems that developed is not integrated for the purpose of establishing a relationship between the customer service in this case the general public, fishermen, fish farmers and partners associated with Department of Marine and Fisheries. Web based information system has not been providing information and services to the public, especially fishermen, limited support facilities services also make the interaction between Department of Marine and Fisheries Customer is not going well and the lack of time to prepare human resources who actually prepared and understanding of e-government by applying CRM models so that the development of e-government towards good governance is achieved